Ispol'zovanie dannyh kliniko-laboratornogo kontrolja v sisteme upravlenija processom podgotovki v zimnih ciklicheskih vidah sporta (na primere biatlona) - Rybina, I.; Sinichenko, R.; Shirkovets, Y. (Science in Olympic Sport, 2020)
Objective. To determine the possibilities of managing training process of highly skilled representatives of winter cyclic sports events on the basis of the analysis of the complex of clinical and laboratory indices in the dynamics of the preparatory period. Methods. Analysis of modern literature data, the results of laboratory and pedagogical examinations of athletes; statistical methods of data processing. Results. The article presents the results of the analysis of association between the indices of actually performed training loads and the data of the metabolic response of the body of highly skilled female biathletes on the basis of clinical and laboratory control data. Pedagogical data characterizing the training process were compared with the characteristics of the metabolic response to performed loads. Conclusion. Revealed as a result of conducted study statistical associations between training load intensity and direction and metabolic response of female athlete body may be used for elaboration of individual plans and efficient management of training process.